2022
DOI: 10.3390/pharmaceutics14102039
|View full text |Cite
|
Sign up to set email alerts
|

Development of Thermosensitive and Mucoadhesive Hydrogel for Buccal Delivery of (S)-Ketamine

Abstract: (S)-ketamine presents potential for the management of acute pain and, more specifically, for the prevention of pain associated with care. However, the administration route can be a source of pain and distress. In this context, a smart formulation of (S)-ketamine was designed for buccal administration. The combination of poloxamer 407 and sodium alginate enables increased contact with mucosa components (mucins) to improve the absorption of (S)-ketamine. In this study, rheological studies allowed us to define th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 39 publications
0
4
0
Order By: Relevance
“…17% (w/v), which is usually not resistant to water dilution when applied in mucosal tissue. 28 To overcome this drawback, DAP has been successfully synthesized in our previous study. 14 DAP not only retains the thermosensitive property of P407 but also presents tougher mechanical strength and stronger tissue adhesion.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…17% (w/v), which is usually not resistant to water dilution when applied in mucosal tissue. 28 To overcome this drawback, DAP has been successfully synthesized in our previous study. 14 DAP not only retains the thermosensitive property of P407 but also presents tougher mechanical strength and stronger tissue adhesion.…”
Section: Resultsmentioning
confidence: 99%
“…Among the variants of poloxamers, P407 is widely used as a hydrogel-forming material owing to its low toxicity and high solubility in water; P407 has the lowest hydrogel-forming concentration of ca. 17% (w/v), which is usually not resistant to water dilution when applied in mucosal tissue . To overcome this drawback, DAP has been successfully synthesized in our previous study .…”
Section: Results and Discussionmentioning
confidence: 99%
“…Furthermore, the synthesized formulation showed a promising in vitro drug-releasing profile and demonstrated high bioavailability with the fast release. 67 Yan et al reported the hybrid hydrogel of corn fiber gum and soya bean protein to deliver the thermosensitive bioactive components orally. The thermosensitive model component was riboflavin (Vitamin B2).…”
Section: Oral Drug Delivery Systemmentioning
confidence: 99%
“…The selection of appropriate thermosensitive polymer for gelling temperature (32°C) based on the rheological studies of poloxamer 407. Furthermore, the synthesized formulation showed a promising in vitro drug‐releasing profile and demonstrated high bioavailability with the fast release 67 . Yan et al reported the hybrid hydrogel of corn fiber gum and soya bean protein to deliver the thermosensitive bioactive components orally.…”
Section: Applicationsmentioning
confidence: 99%